Vibration analysis of the third rail structure of a mass rapid transit system with structural defects - Paudel, Milan (2022)
The third rail is a critical piece of railway infrastructure that provides a continuous supply of electricity to power mass rapid transit trains. The vibration of the third rail may excite different resonant modes and affect its structural integrity and reliability by degrading the mechanical properties leading to the damaged or missing structural components. This paper examines vibrational characteristics of the third rail of Singapore Mass Rapid Transit system with damaged and missing structural components. Using the mathematical model, the first five, pin‐to‐pin modes of vibration and natural frequencies were identified and compared with modal and harmonic response obtained from ANSYS finite element models. A good agreement was observed between the analytical and numerical solutions. The study was further extended to study the sagging of the third rail due to structural failure and its impact on collector shoes. It was found that the structural defects could produce resonance modes below 5 Hz. In addition, the sagging and contact force on collector shoes increased by multiple folds when more than 2 claw structures are broken. The methods and the results presented in this article can be used as a tool for predictive maintenance by detecting possi-ble structural failure or defects.